A Study of Inter-Agencies Cooperation in Border Governance of Nepal - Upreti, Yukesh (Journal of APF Command and Staff College, 2022)
Coordinated border management (CBM) refers to a coordinated approach by border agencies, both domestic and international for achieving efficiencies by facilitating trade and travel flows, with maintaining a balance with compliance requirements. The core objective of this paper is to identify governmental agencies cooperation for border governance of Nepal. For the purpose of understanding inter agency cooperation the research uses both qualitative and quantitative approach with descriptive design using both primary and secondary data. The findings show that there are 12 ministries at federal level and 14 departments with 670 borderline agencies in Nepal. The central ministry, departments, regional offices, district offices and borderline offices are the hierarchical system in intra- agencies. At national level there are different working groups and committee form different ministry. At district level, District Administration Office plays a lead role for local border management by instructing and upervising others agencies in interagency coordination. In order to maintain peace, security and curtail cross border crime, the security agencies are having cordial cooperation by exchanging high level information exchange, sharing of work, regular training and joint inspection by constructing different working groups. The study suggests establishing a national border management policy to incorporate all tiers agencies by constructing national border management Authority to coordinate all agencies from central level to local level which reduce unnecessary work duplication by amending relevant statutes.